2018
DOI: 10.1111/cpr.12515
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG4 promotes tumour growth by sponging miR‐224‐3p and predicts poor survival and recurrence in human osteosarcoma

Abstract: Our findings demonstrated that LncRNA SNHG4 promoted tumour growth by sponging miR-224-3p and represented a poor prognostic factor in patients with osteosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
97
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 25 publications
4
97
0
Order By: Relevance
“…Differential expression of a certain gene in patients and healthy participants indicated its involvement in diseases. In a recent study Xu et al reported that SNHG4 was downregulated in osteosarcoma and its overexpression promoted cancer cell proliferation and predicted the recurrence and poor survival of osteosarcoma patients [13]. In this study, we analyze TCGA dataset and observed the downregulation of SNHG4 in AML.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Differential expression of a certain gene in patients and healthy participants indicated its involvement in diseases. In a recent study Xu et al reported that SNHG4 was downregulated in osteosarcoma and its overexpression promoted cancer cell proliferation and predicted the recurrence and poor survival of osteosarcoma patients [13]. In this study, we analyze TCGA dataset and observed the downregulation of SNHG4 in AML.…”
Section: Discussionmentioning
confidence: 78%
“…Accumulative evidence suggests that some miRNAs, such as miR-10a, can target PTEN to promote the development of cancer [12]. Small nucleolar RNA host gene 4 (SNHG4) is a recently characterized long non-coding RNA (lncRNA) in osteosarcoma [13]. By analyzing TCGA dataset, we observed the downregulation of SNHG4 in AML.…”
Section: Introductionmentioning
confidence: 92%
“…Dysregulation of lncRNA MEG3 could act as a potential predictor of the progression and poor prognosis of osteosarcoma [10], and overexpression of lncRNAs UCA1 and TUG1 are essential in the poor prognosis of osteosarcoma [11,12]. In addition, SNHG4 promotes tumor growth and is a predictor of poor survival and recurrence in human osteosarcoma [13]. HNF1A-AS1 is a negative prognostic biomarker that promotes tumorigenesis and progression in osteosarcoma [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, dysregulation of lncRNAs have been shown to be involved in carcinogenesis and tumour development and can be used as a cancer therapeutic or prognostic biomarker [21][22][23]. Currently, we observed that LINC-PINT expression in NSCLC tissues and cell lines were downregulated.…”
Section: Discussionmentioning
confidence: 77%